Preterm birth phenotypes in women with autoimmune rheumatic diseases: a population‐based cohort study. (31st October 2019) - Kolstad, KD; Mayo, JA; Chung, L; Chaichian, Y; Kelly, VM; Druzin, M; Stevenson, DK; Shaw, GM; Simard, JF
Abstract : Objective: To investigate preterm birth (PTB) phenotypes in women with different autoimmune rheumatic diseases in a large population‐based cohort. Design: Retrospective cohort study. Setting: California, USA. Population: All live singleton births in California between 2007 and 2011 were analysed. Patients with autoimmune disease at delivery were identified by International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM), codes for systemic lupus erythematosus (SLE), systemic sclerosis (SSc), rheumatoid arthritis (RA), polymyositis/dermatomyositis (DM/PM), and juvenile idiopathic arthritis (JIA). Methods: Maternally linked hospital and birth certificate records of 2 481 516 deliveries were assessed (SLE n  = 2272, RA n  = 1501, SSc n  = 88, JIA n  = 187, DM/PM n  = 38). Multivariable Poisson regression models estimated the risk ratios (RRs) for different PTB phenotypes (relative to term deliveries) for each autoimmune disease compared with the general obstetric population, adjusting for maternal age, race/ethnicity, body mass index, smoking, education, payer, parity, and prenatal care. Main outcome measures: Preterm birth (PTB) was assessed overall (20–36 weeks of gestation) and by subphenotype: preterm prelabour rupture of membranes (PPROM), spontaneous birth, or medically indicated PTB. The risk of PTB overall and for each phenotype was partitioned by gestational age: early (20–31 weeks of gestation) and late (32–36 weeks of gestation). Results: Risks for PTB were elevated for each autoimmune disease evaluated: SLE (RR 3.27, 95% CI 3.01–3.56), RA (RR 2.04, 95% CI 1.79–2.33), SSc (RR 3.74, 95% CI 2.51–5.58), JIA (RR 2.23, 95% CI 1.54–3.23), and DM/PM (RR 5.26, 95% CI 3.12–8.89). These elevated risks were observed for the majority of PTB phenotypes as well. Conclusions: Women with systemic autoimmune diseases appear to have an elevated risk of various PTB phenotypes. Therefore, preconception counselling and close monitoring during pregnancy is crucial. Tweetable abstract: This study found that women with systemic autoimmune diseases have an elevated risk of preterm birth phenotypes. Tweetable abstract: This study found that women with systemic autoimmune diseases have an elevated risk of preterm birth phenotypes.